1993
DOI: 10.1002/ijc.2910550522
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐globulin modulates growth of EBV‐derived B‐cell tumors in scid mice reconstituted with human lymphocytes

Abstract: The effect of weekly gamma-globulin injection on the development of human B-cell tumors was studied in 120 mice with severe combined immunodeficiency (SCID). The mice were injected intraperitoneally (i.p.) with human peripheral mononuclear cells (PBMC) from 6 different Epstein-Barr virus (EBV)-seropositive donors. Animals repopulated with cells from 5 donors received gamma-globulin or saline for 20 weeks and were followed up to 24 weeks after reconstitution. A delay in the appearance of fata EBV-derived human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is generally believed that cytotoxic T cells provide the main defense against symptomatic EBV infection and proliferation of EBV‐infected memory B cells (21). It is of interest to note, however, that anti‐EBV antibodies and human immunoglobulin preparations (which contain anti‐EBV antibodies) have been implicated as protective against PTLD in mouse SCID models (22,23), high viral loads in humans (24), and possibly against development of EBV infection/PTLD in pediatric and adult solid organ allograft recipients (16,25,26). Given that IVIG is occasionally used for treatment of EBV or CMV infections, it is possible that these treatments could influence the detection of anti‐EBV antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that cytotoxic T cells provide the main defense against symptomatic EBV infection and proliferation of EBV‐infected memory B cells (21). It is of interest to note, however, that anti‐EBV antibodies and human immunoglobulin preparations (which contain anti‐EBV antibodies) have been implicated as protective against PTLD in mouse SCID models (22,23), high viral loads in humans (24), and possibly against development of EBV infection/PTLD in pediatric and adult solid organ allograft recipients (16,25,26). Given that IVIG is occasionally used for treatment of EBV or CMV infections, it is possible that these treatments could influence the detection of anti‐EBV antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…As originally demonstrated by Mosier et al (20), and confirmed in this and other reports (22,23,25), SCID mice inoculated with PBL from EBV-seropositive donors or with human EBV-transformed B cell lines rapidly develop lethal human EBV-induced lymphoproliferations with characteristics similar to those arising in immunocomproraised patients. Recently, several groups have used this preclinical model to explore the potential of gamma globulin (30), mAbs directed against human CD21, CD23, CD24, and CD40 B cell antigens (31)(32)(33), low dose IL-2 treatment (34), and imexon (35) in the treatment of human EBV-induced lymphoproliferations developing in the SCID mouse.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to LMPs, it has been shown that these molecules are mainly cytoplasmic ; but at least LMP1 spans the plasma membrane (Hennessy et al, 1984), and antibodies to this antigen could be functionally important. LMP1 also has been implicated in apoptotic events protecting EBV-infected cells from cell death by up-regulating expression of the cellular oncogene bcl-2 (Henderson et al, 1991), and low levels of anti-LMP1 antibodies were previously found in gammaglobulin preparations (Abedi et al, 1993). It is also possible that a mixture of antibodies against antigens belonging to the latent and replicative forms of EBV, present in gammaglobulin preparations, are necessary for prevention of tumor formation; therefore, examination of the therapeutic effect of antibodies against single antigens would be of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…One donor was used on 2 occasions for PBMC donation. Donor selection was based on previous experiments using his PBMCs for reconstitution of SCID mice, which resulted in a complete prevention of EBV-derived human B-cell tumors following gammaglobulin treatment (Abedi et al, 1993). On both occasions, all SCID mice (n 5 163) were injected i.p.…”
Section: Pbmc Donorsmentioning
confidence: 99%
See 1 more Smart Citation